Indian summer - Kanai, Mieko, 1947- (Cornell East Asia series, 2012)
Indian Summer (Koharu biyori) is the title of a relatively short novel by Kanai Mieko (b. 1947), recognized by critics both inside and outside Japan as one of the most important Japanese writers of recent decades. The work brilliantly demonstrates Kanai's light-hearted wit in addition to her penchant for biting commentary on conservative elements in Japanese society. Kanai is also an acclaimed essayist, film critic, literary critic, and poet, and has produced a steady output of high-quality material since making her literary debut in her teens.